UK Silvoarable Network data - Burgess, Paul J.; Pilbeam, D. J.; Hart, B. J.; Beaton, A.; Seymour, Ian Leslie; Corry, D.; Evans, R. J.; Incoll, L. D. (Cranfield University, 2025)
Silvoarable agroforestry (the intercropping of trees and arable crops) can diversify farm incomes, increasing tree planting and improve farm biodiversity. In 1992 a silvoarable experiment, comprising three replicate blocks of four poplar (Populus spp.) hybrids (at a spacing of 10 m x 6.4 m) and three arable treatments, was established by Cranfield University in Bedfordshire, Leeds University in West Yorkshire, and the Royal Agricultural University in Gloucestershire. [The associated report describes the results from the experiment for the four-year period from April 1999 to April 2003. It covers the effects on tree growth, crop yields, economics, understorey vegetation, and the number and diversity of ground invertebrates.]
Keywords: Silvoarable agroforestry; Poplars; Biodiversity; Crop yields; Arable farming